'[Selling]': Gender capital in the commerce of men's underwear on Reddit. Issue 2 (1st August 2022) - Dashiell, Steven L.
This article looks at the discursive values of concepts in the homosocial attraction of underwear to men. The Reddit space 'r/underwear' is a locale where men can buy and sell underwear from others. Rather than the selling of unused or unwanted products, a principal focus of the space is the selling of used underwear. I examine the discursive elements that occur on the page, and how the sellers work to present the underwear for the presumed purpose of selling them ‐ discussing how these actions reinforce a sense of gender capital. There is a clear provocativeness in the ads, where the purpose is to sell the underwear and demonstrate the masculinity of the seller. Further, the heightened sense of masculinity is provided by the descriptive terms, given the use of concepts such as 'musky', 'sweaty' and 'cum' to reinforce the used nature of the underwear. I speculate that the choice of words serve as a reinforcement of the outward manhood of the seller, relating a 'tough' masculinity even though the selling of underwear is a homoerotic venture. I note how there is a sense of 'selling masculinity' through the gender capital linked to one's underwear, adding to conversations of the symbolic value of manhood.